Cortisol awakening response and testosterone jointly affect adolescents' theory of mind - Wang, Huagen; Zhang, Sihui; Wu, Simeng; Qin, Shaozheng; Liu, Chao (Hormones and behavior, 2022)
Adolescence is a critical period for the maturation of neurobiological processes and hormone secretion. Recent studies on the dual-hormone hypothesis have indicated that basal cortisol and testosterone jointly affect dominant and aggressive behavior among adolescents and adults. Whether this hypothesis applies to prosocial-related understanding of others' mental states remains unclear. The present study investigated associations between basal testosterone, basal cortisol (and cortisol awakening response [CAR]), and the cognitive/affective theory of mind (ToM) in 243 adolescents (67.9 % male, aged 14 to 17 years, Mage = 16.09, standard deviation = 0.62). Cognitive ToM (cToM) and affective ToM (aToM) were assessed with a cartoon story reasoning task: In the cToM condition, participants viewed a comic strip story and needed to predict what would happen based on a character's intentions, and in the aToM condition, they viewed a comic strip of two characters interacting and needed to think about what would make the protagonist feel better. The results showed that basal testosterone and basal cortisol did not interact with each other to affect the performance of ToM, either in terms of ToM accuracy or response speed. However, under the condition of low CAR, testosterone is associated with the fast performance of cToM, although the interaction of testosterone and CAR occurred only in female adolescents. Overall, our data provide new evidence for the dual-hormone hypothesis and further extend the hypothesis to social understanding.